2009
DOI: 10.1111/j.1439-0264.2009.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Stretching on Expressions of Muscle Specific Transcription Factors MyoD, Myf‐5, Myogenin and MRF4 in Proliferated Myoblasts

Abstract: We examined expression of four important members of myogenic regulatory factors (MRFs) in the myoblasts both at mRNA and protein levels, which were subjected to mechanical stretching in in vitro condition. Our results showed that MyoD expression existed both in the stretch and in the control group at all time periods of the mechanical stimulus. Myf-5 expressed only at early stage of the stretch group. Although mRNA and protein expressions of myogenin and MRF4 were detected both in the stretch and in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…Similarly, in the present study, we identified significant (P < 0.05) and positive correlation between the expression of DLK1 and IGF-I. Abe et al (2009) indicated that IGF-I expression showed the same trend as that of MyHC 2b from prenatal days 16-18. The increase in MyHC 2b expression enlarged the muscle fiber diameter; thus, IGF-I may be a regulatory factor associated with the growth of muscle and muscle fiber diameter enlargement.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, in the present study, we identified significant (P < 0.05) and positive correlation between the expression of DLK1 and IGF-I. Abe et al (2009) indicated that IGF-I expression showed the same trend as that of MyHC 2b from prenatal days 16-18. The increase in MyHC 2b expression enlarged the muscle fiber diameter; thus, IGF-I may be a regulatory factor associated with the growth of muscle and muscle fiber diameter enlargement.…”
Section: Discussionsupporting
confidence: 60%
“…22,23 In addition, they are able to rearrange themselves on the culture substrate, 24,25 which is consistent to the principle of actin fiber reorganization observed in many cell types. [26][27][28][29][30] Strikingly, however, neither the application of a uniform strain field in all directions, the equibiaxial CTS, [31][32][33][34][35][36] nor uniaxial CTS applied parallel to the long axis of cells 37 seem to support myogenesis. This experimental evidence has fueled the currently established concept of impairment of differentiation by mechanical stimulation of mammalian myoblastic precursors.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have given comparable results: the genes MyoD and myf-5 were up-regulated early in the stretching process (first 12 h), whereas myogenin and MRF-4 were up regulated after 24 h of stretching before returning to control levels thereafter (Abe et al 2009). Boonen et al (2010), however, have presented seemingly contradictory results for the effects of stretching on muscle maturation and regeneration.…”
Section: Molecular Regulation Of Satellite Cellsmentioning
confidence: 78%